Early age bond stress-slip behaviour of macro-synthetic fibre reinforced concrete. (27th September 2021) - Watts, Murray J.; Amin, Ali; Bernard, E. Stefan; Gilbert, R. Ian; Facconi, Luca
Highlights: Early age bond vs slip test results are conducted on Macro-Synthetic FRC. Fibres improve the peak bond strength in reinforced concrete. Fibres improve the bond strength at low slips (in the serviceability range). A simple model founded on the fib MC2010 is adapted. Abstract: The magnitude of bond stress that exists between concrete and steel reinforcement heavily influences the width and spacing of cracks. An understanding of the bond stress available is important when estimating deformations and crack widths in structural concrete. Experimental studies and modelling have shown that the inclusion of fibres improves bond characteristics in structural concrete. These studies have focused on the strength criterion in mature aged concretes containing steel fibres. No early age bond test results currently exist for macro-synthetic fibre reinforced concrete (FRC). In this paper, the results of an experimental campaign are presented on the bond-slip behaviour of macro-synthetic fibre reinforced concrete (containing either 0, 4 or 8 kg/m 3 of fibres) tested at 1, 3, 7, 14, 28 and 90 days using standard pull-out tests. The tests are complimented with a suite of material characterisation tests. Furthermore, a simple model founded on previous approaches is presented to describe the ascending portion of the bond stress – slip relationship for FRC. It is concluded that the early age bond strength is slightly improved through the addition of macro-synthetic fibre reinforcement. On the other hand, the early age bond stiffness of reinforced concrete is substantially improved through the addition of macro-synthetic fibre reinforcement.